Entrepreneurship Theory: New Challenges and Future Prospects - Alexander Chepurenko (Foresight and STI Governance)
The paper analyses the problems of contemporary entrepreneurship theory which scientists are confronting in recent years. There are arguments given in favour of a broad definition of entrepreneurship as ‘emergence of new economic activity’. The starting point of research on entrepreneurship research is the question, ‘how, why, and when do entrepreneurial firms explore and exploit entrepreneurial opportunities?’ According to the author of this paper, it thus becomes possible to redefine the subject of the discipline, which in turn enables a sustainable development of the theory, and a refocusing on new areas such as social and institutional entrepreneurship. The paper forecasts a shift in research on entrepreneurship beyond Western societies to encompass the so-called transitional economies and emerging markets. These countries have some important contextual differences which affect the practices of entrepreneurship and these are discussed here. Contextual differences justify the importance of investigating new institutions and actors which might become challenging subjects of entrepreneurship theory in future.The paper also discusses the agenda of entrepreneurship research in Russia, explains the reasons for the relatively weak development of Russian entrepreneurship theory, and suggests policies to improve this situation. The author stresses the changes in methods and research design and the new possibilities and empirical data sources resulting from  the latest advancements in IT and big data. In particular, more intensive research and demand for this research will likely emerge because of the increasing availability of techniques for collecting and analysing big data. The author anticipates the increasing importance of international comparative studies conducted by large project teams, and of longitudinal projects to elaborate realistic recommendations for civil society, national governments, and international organizations.